SYSTEMIC JIA-ASSOCIATED LUNG DISEASE: A MULTICENTER ANALYSIS OF CLINICAL FEATURES,TREATMENT CHALLENGES AND OUTCOMES - Unal, D.; Cam, V.; Konte, E. Kilic; Celikel, E.; Ozdel, S.; Gurgoze, M. K.; Ozen, S. (Elsevier, 2025)
[Abstract Not Available]
Keywords: biological DMARD; Innate immunity